LOVE OF MONEY, RELIGIUSITAS DAN PENGGELAPAN PAJAK (Studi Kasus Pada Mahasiswa Dan Pekerja) - Arini Tri Agustine, Arini Tri Agustine; Dina Ayu Lestari, Dina Ayu Lestari; Eramita Ufitia, Eramita Ufitia; Karyn Fellya Zahwa P.F, Karyn Fellya Zahwa P.F; Saskia Seftiani, Saskia Seftiani (Jurnal Akuntansi, Auditing dan Keuangan Syariah, 2022)
There have been many cases of tax evasion in Indonesia, giving rise to different perceptions for everyone. Currently, most countries depend on tax revenues. Tax relief receipts are important for financing government spending. On the other hand, taxes are the main source of government revenue. This is common, especially among developing countries like Indonesia. However, several cases of tax evasion among taxpayers need to reveal what factors influence the attitude and behavior of taxpayers. Most Indonesian people's daily lives refer to their religion, so religion has an important role to influence their actions and views. The love of money is something that can influence someone in tax evasion. This study aims to determine whether or not the influence of the Love of Money on tax evasion, and determine whether or not religious influence on tax evasion. The population in this study are individual taxpayers (students and workers). The data used in this study is primary data by distributing questionnaires to individual taxpayers including students and workers. The sample in this study was 100 respondents. Analysis prerequisite tests include normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used to test the hypothesis is multiple linear regression analysis. The results of this study indicate that love of money has no effect on tax evasion as evidenced by the significance value and religion has an effect on tax evasion as evidenced by the significance value.